Health Service Delivery Complexities in Mutare Urban, Manicaland Zimbabwe (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This research study sought to identify the health service delivery challenges in urban areas using Mutare as a point of reference. Interviews, focus group discussions and observations were used to collect data from selected residents of Mutare city. Mutare city is experiencing poor service provisions and serious health service delivery challenges. This is witnessed by high doctor to patient ratio, high infant and maternal mortality rates as well as high incidences of malaria and other infectious diseases. The challenges are not limited to drugs and medical facilities, medical staff, transport, distance and referral mechanism, costs and financing of services culture and attitudes, corruption and bribery. Recommendations were made regarding the possible adjustment to existing health strategies and policies used in Zimbabwe, for the improvement of the health service delivery system of the city of Mutare. New strategies were also recommended for the improvement of the health system of the city. Lastly, some proposals were made for further research on the health service delivery challenges in rural areas so that comparisons are made to see whether the challenges are the same.